Comparison of Mono Therapy with Tazobactam Versus Multi Drug Therapy for Treatment of Perforated Appendix in Children - Aman, Nadir; Munir, Asad; Bashir, Kashif; Rafique, Mariam; Mahwish Noor ul Haq,; Zafer, Zuha (Indus Journal of Bioscience Research, 2024)
Introduction: Appendicitis stands as the predominant surgical emergency among pediatric patients. Despite its high occurrence rate, there remains a lack of agreement concerning the diagnostic and treatment approaches for this condition. This study aims to assess and compare the surgical results of open appendectomy in children with perforated appendicitis, utilizing either a perioperative multiple antibiotic regimens or a single antibiotic regimen. Patients and Methods: The investigation was carried out on pediatric patients who underwent open appendectomy due to perforated appendicitis at the Pediatrics Surgery Department in Mayo Hospital between December 2023 and June 2024. A total of 74 children were enrolled in the research. One group, Group A, received monotherapy with piperacillin/tazobactam, while another group, Group B, received multiple drug therapy with Metronidazole and Meropenem. Results: The mean age of patients in group A was 9.76±2.488 years and in group B was 9.86±2.406 years. In group-A (Tazobactam monotherapy), intra-abdominal collection was noted in 4(10.8%) patients and 3(8.1%) patients in group-B (Multi-drug therapy) with a p-value of 0.691. The mean hospital stay in Tazobactam monotherapy group was 7.92±0.829 days and in Multi-drug therapy group as 7.16±0.727 days (p<0.05). Conclusion: In the current study population, the use of monotherapy antibiotic treatment for perforated appendix in children demonstrated comparable effectiveness to triple antibiotic therapy in mitigating infectious morbidities, suggesting that the choice between these two approaches may not significantly impact the clinical outcomes of patients in this particular cohort.